Trignometry - 5

Geometry Level 3

Given that, A n = sin n θ + cos n θ A_n = \sin^{n}\theta + \cos^{n}\theta where n is whole number and θ ϵ R \theta \epsilon \mathbb{R} .

If, A n 2 A n = ( sin 2 θ cos 2 θ ) A λ A_{n-2} - A_n =( \sin^2\theta \cos^2\theta ) A_{\lambda} . What is the value of λ \lambda ?

n - 2 n - 4 n - 3 n - 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Nasr
Oct 15, 2014

s i n n 2 θ + cos n 2 θ sin n θ cos n θ = ( sin 2 θ c o s 2 θ ) A λ sin^{n-2} \theta\ + \cos^{n-2} \theta\ - \sin ^{n} \theta\ - \cos^{n} \theta =(\sin^{2} \theta\\cos^{2} \theta)\ A_{\lambda}

A λ = sin n 4 θ cos 2 θ + cos n 4 θ s i n 2 θ sin n 2 θ cos 2 θ cos n 2 θ sin 2 θ A_{\lambda}=\frac {\sin^{n-4}\theta}{\cos^2\theta}+\frac {\cos^{n-4}\theta}{sin^2\theta}-\frac {\sin^{n-2}\theta}{\cos^2\theta}-\frac {\cos^{n-2}\theta}{\sin^2\theta}

A λ = sin n 4 θ sin n 2 θ c o s 2 θ + cos n 4 θ cos n 2 θ s i n 2 θ A_{\lambda}=\frac {\sin^{n-4}\theta-\sin^{n-2}\theta}{cos^2\theta}+\frac {\cos^{n-4}\theta-\cos^{n-2}\theta}{sin^2\theta}

A λ = sin n 4 θ ( 1 sin 2 θ ) c o s 2 θ + cos n 4 θ ( 1 cos 2 θ ) s i n 2 θ A_{\lambda}=\frac {\sin^{n-4}\theta (1-\sin^2\theta)}{cos^2\theta}+\frac {\cos^{n-4}\theta (1-\cos^2\theta)}{sin^2\theta}

Knowing that 1 sin 2 θ = cos 2 θ 1-\sin^2\theta=\cos^2\theta and 1 cos 2 θ = s i n 2 θ 1-\cos^2\theta=sin^2\theta ;

A λ = sin n 4 θ + cos n 4 θ A_{\lambda}=\sin^{n-4}\theta+\cos^{n-4}\theta

Then λ = n 4 \lambda=\boxed{n-4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...